Comparison of Blood Glucose Level in Different Trimester with Stress, Anxiety Depression among Young Pregnant Females - Rozina Mangi, Jamshed Warsi, Noman Sadiq, Hammad Raziq, Ashfaque Ahmed Buriro, Zulfiqar Ali Laghari, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Psychological health affects numerous physiological processes of the body. The psychological well-being of pregnant women is a global concern. Aim: To compare the blood glucose level (random) in normal versus stress, depression and anxiety among pregnant women (Trimester wise) in district Hyderabad. Methods: A cross-sectional study (survey-based) was conducted in a fixed time frame. The pregnant women were randomly selected and segregated into three groups (trimester wise). The sample size (n) was 123. Random blood glucose level was measured by using the check UC-1001. Stress, anxiety and depression were analyzed by using a valid questionnaire DASS-21. Student t-test was employed as appropriate. Data is shown as mean±standard deviation. Results: Blood glucose level was observed significantly higher (P-value: 0.0004, 0.009 and 0.046) in stressed women (137.82 ±28.94, 142.60 ±40.34 and 126.82 ±35.92) as compared to normal (107.6 ±18.01, 115.05 ± 18.68 and 105.53 ±21.56). Similarly, the blood glucose level was observed higher (P- values: 0.043, 0.065 and 0.078 in depressed women (128.62 ±29.85, 136.79 ±37.10 and 122.44 ±33.41) as compared to normal (105.62 ±13.71, 112.22 ±24.60 and 101.22 ±18.66). An elevated blood glucose level (P-value in First, Second and Third trimester was 0.230, 0.065 and 0.900 respectively) was observed in those who were suffering from Anxiety (125.63 ±29.27, 136.79 ±37.10 and 121.81 ±32.36) as compared to those whose blood glucose level is normal (107.25 ±17.85, 112.22 ±24.61 and 123.66 ±37.04). Conclusion: An elevated blood glucose level was observed in all three trimesters in stressed, depressed and anxious pregnant women. Keywords: Anxiety, Depression, Stress, Blood Glucose. Trimester